A Factorial Design Approach for Hydrothermal Synthesis of Phase‐Pure AgInO2: A Parametric Optimization Study. (30th December 2019) - Beatriceveena, T. V.; Sree Rama Murthy, A.; Murugesan, S.; Prabhu, E.; Gnanasekar, K. I.
Abstract: Owing to a wide range of industrial applications and fundamental importance, delafossite compounds have gathered tremendous interest in research community. In this study, the formation of hexagonal nanoplates of AgInO2 mainly dominated by (00l) facets with no metallic Ag impurity, reported using a facile hydrothermal route at 180 °C using KOH as mineralizer by adopting a factorial design approach. Rietveld analysis of the powder XRD pattern and SAED confirms the rhombohedral system of AgInO2 . FE‐SEM image shows a uniform hexagonal plate‐like morphology with an average width of about 300 nm and thickness of 70 nm. XPS and EDX analysis confirm potassium ion free AgInO2 . A specific surface area of about 48.5 m 2 g −1 is arrived from N2 adsorption studies. Temperature‐dependent AC impedance measurements revealed an activation energy of 0.24 eV/f.u. Further, TG‐DTA studies found that the compound is stable in air up to 595 °C. Abstract : Rein in den Reaktor, rein aus dem Reaktor : Faktorielle Versuchsplanung wurde genutzt, um phasenreines AgInO2 über eine Hydrothermalroute zu synthetisieren. Silber‐ und Indiumnitrat mit KOH als Mineralisator förderten die Bildung von AgInO2 in Form hexagonaler Nanoplättchen. Die Optimalbedingungen von 180 °C und 4 m KOH bildeten die entscheidende Kombination zum Erhalt der reinen Phase.